The Role of Immigration in the Health of Lesbian, Gay, Bisexual, and Transgender Older Adults in the United States. (July 2019) - Lee, Jane J.; Kim, Hyun-Jun; Fredriksen Goldsen, Karen
Lesbian, gay, bisexual, and transgender (LGBT) aging research is growing around the globe. Yet, few studies have examined the interconnectedness of different populations and cultures. This study examines whether LGBT foreign-born older adults experience greater health disparities than their U.S.-born counterparts. We conducted a cross-sectional analysis of the National Health, Aging, and Sexuality/Gender Study: Aging with Pride from 2014, which assessed measures of health and well-being among LGBT adults aged 50 years and older ( n = 2, 441). We compared sociodemographic characteristics, health-care access, health behaviors, and health outcomes between foreign-born and U.S.-born participants. Foreign-born LGBT older adults reported greater socioeconomic disadvantage and higher levels of experiencing barriers to health-care access than U.S.-born LGBT older adults. Groups did not significantly differ in health behaviors and health outcomes when controlling for sociodemographic factors. Greater understanding of the mechanisms that shape the relationship between migration and health among the LGBT population is warranted.